PUDARNYA EGALITARIANISME PADA ARSITEKTUR BALI AGA - Suyoga, I Putu Gede (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
The architecture of Bali Aga is an artifact in Balinese civilization. The concept of social relation of kesamen as an egalitarian tradition of Bali Aga society, besides forming equality in social in- teraction, apparently also affect architectural spatial and building in Bali Aga villages. This study uses qualitative method with analytical descriptive approach and data collection with observation and documentation. Informant determination was done by purposive sampling. Data analysis is based on Gramsci’s theory of domination and hegemony, as well as the theory of adaptation. The result of the research shows the form of building, spatial arrangement pattern, building material, and circulation system, have similarities between buildings with each other, so also in the layout of village settlements is relatively the same as applying linear pattern ‘straight line’ kaja-kelod with the center of communal activity in the center of the village. This uniformity was established for a long time, before it finally faded due to Bali Majapahit’s cultural pressures in the Balinese period. The architectural identity struggle produces a new artifact of neo architecture Bali Aga as a Bali Aga hybrid architecture with Bali Majapahit who contribute in the area of Bali Aga villages. The results of architectural adaptation can be observed in architecture parhyangan, pawongan, public, and village spatial.